Activities of protein components in bean seeds of Kazakhstan, russian and other accessions (ҚазҰУ Хабаршысы. Биология сериясы, 2016)
Common bean specimens (Phaseolus vulgaris L.) of Kazakhstan, Russian and other foreign collections have been studied for protein content, lectin and proteinase inhibitor activities. All studied specimens have revealed high protein content (23.2% -30.8%) and lectin activity with its relation to particular genotype and origin. In course of the study on the lectin activity, a wide range of variations for this parameter has been found for twelve bean specimens. The maximum difference between the specimens has reached 17.5 mg / mL with highest values of 38.3 and 55.8 mg/mL. Two varieties, "Jubileynaya White" and "Zhuravushka" of Russian selection, one local variety "Assol" and "The Iranian" of Iranian selection have indicated the most expressed lectin activities. Trypsin inhibitor activity has appeared to be approximately twice higher than that of the chymotrypsin, and the highest inhibitor activity of trypsin and chymotrypsin has been detected in the samples with the highest lectin activities. Apart from investigating protein components activity, promising specimens have been identified by testing the highest proteins content, lectin and proteinase inhibitor activities which may serve as powerful sources of bean protein components with reference of their effects on different cell models, to develop biotechnological approaches for extraction and application to agriculture.